Clinical correlates, ethnic differences, and prognostic implications of perivascular spaces in transient ischemic attack and ischemic stroke - Lau, K; Li, L; Lovelock, C; Zamboni, G; Chan, T; Chiang, M; Lo, K; Küker, W; Mak, H; Rothwell, P (American Heart Association, 2017)
BACKGROUND AND PURPOSE: Perivascular spaces (PVSs) are considered markers of small vessel disease. However, their long-term prognostic implications in transient ischemic attack/ischemic stroke patients are unknown. Ethnic differences in PVS prevalence are also unknown. METHODS: Two independent prospective studies were conducted, 1 comprising predominantly whites with transient ischemic attack/ischemic stroke (OXVASC [Oxford Vascular] study) and 1 comprising predominantly Chinese with ischemic stroke (University of Hong Kong). Clinical and imaging correlates, prognostic implications for stroke and death, and ethnic differences in basal ganglia (BG) and centrum semiovale (CS) PVSs were studied with adjustment for age, sex, vascular risk factors, and scanner strength. RESULTS: Whites with transient ischemic attack/ischemic stroke (n=1028) had a higher prevalence of both BG and CS-PVSs compared with Chinese (n=974; >20 BG-PVSs: 22.4% versus 7.1%; >20 CS-PVSs: 45.8% versus 10.4%; P<0.0001). More than 20 BG or CS-PVSs were both associated with increasing age and white matter hyperintensity, although associations with BG-PVSs were stronger (all P<0.0001). During 6924 patient-years of follow-up, BG-PVSs were also independently associated with an increased risk of recurrent ischemic stroke (adjusted hazard ratio compared with <11 PVSs, 11-20 PVSs: HR, 1.15; 95% confidence interval, 0.78-1.68; >20 PVSs: HR, 1.82; 1.18-2.80; P=0.011) but not intracerebral hemorrhage (P=0.10) or all-cause mortality (P=0.16). CS-PVSs were not associated with recurrent stroke (P=0.57) or mortality (P=0.072). Prognostic associations were similar in both cohorts. CONCLUSIONS: Over and above ethnic differences in frequency of PVSs in transient ischemic attack/ischemic stroke patients, BG and CS-PVSs had similar risk factors, but although >20 BG-PVSs were associated with an increased risk of recurrent ischemic stroke, CS-PVSs were not.